(3GdhSjW aj TQM GdbGfhf GdJLGQj (B:s (3GdChQGb GdJLGQjI hYedjGJ GdHfhc (B= Mediator in explaining the commercial law : Commercial documents and banks transactions /s - (3GdYcjdj, YRjRs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2018)
(3jJVef gPG GdLRA ef TQMfG dCMcGe GdbGfhf GdJLGQj TQMG hGajG dCMcGe GdChQGb GdJLGQjI hGdYedjGJ GdeUQajI ef bGfhf GdJLGQI GdCQOfj Qbe (B12 (3dSfI (B1966 (3hYdi Pdc SfHMK GdehVhYGJ GdJj fJfGhd TQM CMcGegG aj gPG GdLRA ef eDdafG aj bSejf GdbSe GdChd fNUUg dOQGSI CMcGe GdChQGb GdJLGQjI GdJj fXe CMcGegG bGfhf GdJLGQI GdCQOfj hGdbSe GdKGfj fNUUg dOQGSI CMcGe HYV GdYedjGJ GdeUQajI GdJj fXe CMcGegG GdHGH GdNGeS ef GdcJGH GdKGfj ef bGfhf GdJLGQI GdCQOfj CeG GdYedjGJ GdeUQajI GdJj de jQO dgG PcQ aj gPG GdHGH aSfbhe HOQGSI CMcGegG hab eG JVefJg GdbhGfjf GdebGQfI heG GSJbQ HTCfgG ef CYQGa OhdjI HGYJHGQ Cf GdYedjGJ GdeUQajI ChLOgG hWhQ bhGYOgG GdYQa GdeUQaj(B.s
(3HHdjhLQGajI (B: (3UaMI (B505-511.s
Keywords: (3GdChQGb GdJLGQjIs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs; (3GdYbhO GdJLGQjIs -- (3GdCQOfs; (3GdbGfhf GdJLGQjs -- (3GdCQOfs